Insurgent Attitude: The Shifting Ground of the Afrospora Feminine. - John, Catherine A. (Frontiers: A Journal of Women Studies, 2024)
This essay situates the notion of "attitude" or "plenty plenty-ness" associated with excessive Black femininity in African diaspora US and Caribbean spaces, within the contexts suggested by Sylvia Wynter's "demonic ground," Hortense Spillers' "insurgent ground," as well as Denise Ferreira da Silva's theory of "hacking the subject." I use Ferreira da Silva's statement that Black women "neither comply [with] nor disappear [from]" the hegemonic order to argue for a conception of the Black feminine that rests on the shifting ground between invisibility and disruptive power. This power is both consciously and subconsciously deployed in ways that may seem excessive to outsiders but which fuel both Black feminine energy and artistic expression. This article asks if, rather than being birthed on the plantation, this femininity sits partially outside the frame of what Ferreira da Silva refers to as "the patriarch form"? What if, following from Spillers we read Black female excess as symbolic, insurgent possibility rather than absence?